Crisis Communications Related to Student Learning Implementation in Public Relations Marketing Event Course - Faustyna Faustyna (International Journal Reglement & Society (IJRS), 2023)
This study aims to analyze crisis communication patterns related to the implementation of student learning in the Marketing Event Public Relations course. Crises can threaten the reputation and maintain an organization; therefore, it is important to understand how students can face and handle crises that occur in the context of marketing and public relations activities. Methods This research was conducted using a qualitative approach and involved case studies on students who were taking the course. The research data was obtained through in-depth interviews with students who had experienced a crisis in implementing their learning in the Marketing Event Public Relations course. A qualitative method with Data analysis was carried out using a thematic approach to identify patterns of crisis communication that emerged during the situation. The research findings indicate that there is a pattern of communication involving internal communication between students, communication with teaching lecturers, as well as communication with related external parties. The results of this study provide a deeper understanding of how students face and respond to crisis situations in the context of learning Marketing Event Public Relations. The findings of this research can also provide valuable input for the development of relevant curricula and teaching methods in this course. In conclusion, this research makes an important contribution to the understanding of crisis communication patterns in the context of implementing student learning in the Marketing Event Public Relations course. It is hoped that the suggestions from this research can be used as a basis for increasing the understanding of students, teachers, and practitioners in the field of marketing and public relations in dealing with future crisis situations. Students are expected to be able to develop effective crisis communication skills and apply the knowledge they have acquired in real situations.